Tinjauan Mendalam Tentang Penerapan PSAK 22, PSAK 65, dan PSAK 4: Implikasi dan Strategi Pelaksanaanya (Jurnal Kendali Akuntansi, 2024)
In the modern business era, it is important for companies to understand PSAK and its implications to ensure consolidated financial statements are accurate and in accordance with applicable accounting standards. The aim of this research is to discuss in detail the three Financial Accounting Standards, namely PSAK 22, PSAK 65, and PSAK 4 and their relevance to the preparation of consolidated financial statements. The method used in this research is descriptive qualitative through literature study with secondary data in the form of previous articles. The result of this research is that PSAK 22 discusses the accounting treatment of business combinations in the form of acquisitions or mergers of ownership, whether carried out through the acquisition of shares or net assets. PSAK 65 regulates consolidation criteria and explains consolidation procedures. Meanwhile, PSAK 4 (revised 2009) explains consolidated financial reports and separate financial reports.